Lightweight pile steel in marine environment and production method thereof
By developing a lightweight pile steel with specific components and tissue structures in the marine environment, combining composite trace elements and specific production processes, the materials requirements for high strength, lightweight, corrosion resistance and hydrogen-induced crack resistance in the marine environment are solved, and efficient steel performance improvement is achieved.
Patent Information
- Application Number
- CN202211610465.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The prior art is difficult to provide high-strength, lightweight, corrosion-resistant and hydrogen-crack-resistant steel in marine environments, especially in complex sea areas such as southern my country, which cannot meet the material needs of lightweight structures such as offshore wind power.
A lightweight pile steel in marine environment is used, and its components include C, Si, Mn, V, N, Cu, Ni, Mo, Ta, Re, Cr, REM, Sn, Ti, P and S. Through the addition and synergistic effect of composite trace elements, a corrosion-resistant structure of 70-80% bainite + 15-25% ferrite is formed, and the grain size and distribution of precipitation phase are controlled through specific production processes such as smelting, continuous casting, billet heating, controlled rolling and downline processing.
The steel plate has achieved high corrosion resistance, good mechanical properties and hydrogen-induced crack resistance, the yield strength reaches 500MPa level, the corrosion resistance is improved by 4-13%, and there is no crack in the environment of 40℃×85% RH.
Smart Images

Figure GHA0000009066080000091 
Figure GHA0000009066080000092 
Figure GHA0000009066080000093
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material preparation, and in particular relates to a lightweight pile steel in a marine environment and a production method thereof. Background Art
[0002] The offshore wind farm system is huge and expensive, mainly due to the cost of offshore wind power foundation, installation and operation and maintenance of the wind farm. The cost of wind power foundation accounts for about 20% to 30% of the cost of the entire wind farm. As offshore wind farms gradually move from offshore to deep sea and install larger capacity generators, the foundation cost will increase further. The design and research of low-cost foundation structures is the key to reducing the cost of wind turbines. How to reduce foundation costs is one of the key issues that urgently need to be solved in the entire offshore wind power field, and it is also the focus of offshore wind power developers and research institutions.
[0003] High-strength and ultra-high-strength steel can effectively reduce the weight of wind turbine foundations and wind towers, which is not only conducive to ensuring safety, but also can reduce its own weight, welding workload, material transportation costs and increase bearing capacity. At present, offshore wind turbines mainly use structural steel for marine engineering, and the application standard is GB 712-2011 "Structural Steel for Ships and Marine Engineering", with a yield strength of 355MPa, grades DH36 and EH36, and the delivery state is normalized. With the increase in the number of large wind turbines and the increase in the thickness of the steel plates used, and under the pressure of reducing construction costs, offshore wind power plants in Europe, Japan and other countries have begun to use low-alloy steel plates with a yield strength of 460MPa or 500MPa in batches to reduce the thickness of the steel plates while ensuring costs and structural rigidity. my country's southern seas are the most abundant offshore wind resources and are the focus of my country's medium- and long-term offshore wind power resource development. However, this sea area is also one of the worst marine environments in the world, with the highest corrosion level reaching C5. Compared with other regions, surface ships, ground buildings, equipment and facilities, and offshore floating platforms in this environment will suffer from severe corrosion prematurely even if corrosion protection measures are taken. According to statistics, the failure rate of equipment and facilities in service in my country's southern seas is three times that of other seas and about 10 times that of mainland areas.
[0004] The invention patent with application number 201710075154.0, "A high corrosion resistant low alloy steel suitable for high temperature coastal environment", the invention patent with application number 201611097512.X, "A high strength weathering steel resistant to high humidity and heat marine atmosphere environment", and the invention patent with application number 201611102046.X, "High strength weathering steel resistant to high humidity and heat marine atmosphere environment and preparation method". All of them adopt high Ni system and alloy with elements such as Cu and Mo. The problem is that the cost is high, and due to the high alloying and carbon equivalent, the welding performance has problems, and the risk of hydrogen induced cracking is not considered. The invention patent with application number 201880084248.7, "Steel with excellent hydrogen induced cracking resistance and manufacturing method", proposes a steel for pressure vessels and its manufacturing method that effectively ensures hydrogen induced cracking (HIC) resistance, but it cannot solve the corrosion resistance of steel under marine environment conditions.
[0005] In summary, existing research is all aimed at improving the corrosion resistance of materials in harsh environments, lacking an overall consideration of H resistance. Existing solutions for hydrogen-resistant cracking steel cannot solve the corrosion resistance of steel grades, and for lightweight, corrosion-resistant, and hydrogen-resistant cracking steel materials with a strength of >460MPa, it is difficult to meet the material requirements of lightweight structures such as offshore wind power in complex sea areas such as the southern waters of my country. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to propose a lightweight pile steel for marine environment and a production method thereof, taking into account the mechanical properties and corrosion properties of the steel, with a strength of 500MPa and effectively solving the problem of preventing H-induced cracks.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows: a lightweight pile steel for marine environment, wherein the steel composition comprises, by weight percentage, C: 0.03-0.06wt%, Si: 0.15-0.3wt%, Mn: 0.7-1wt%, V: 0.04-0.06wt%, N: 0.0012-0.016wt%, Cu: 0.3-0.5wt%, Ni: 0.8-1.2wt%, Mo: 0.2-0.4wt%, Ta: 0.01-0.02wt%, Re: 0.01-0.0 2wt%, Cr: 1-1.5wt%, REM: 0.03-0.05wt%, Sn: 0.05-0.1wt%, Ti: 0.001-0.005wt%, P: 0.01-0.02wt%, S: ≤0.005wt%, the balance is Fe and other inevitable impurities; the average grain size of 1 / 4-1 / 8 thickness of the steel plate is 20-30μm, the average grain size in the core of the steel plate is 30-50μm, the steel plate contains 70-80% bainite + 15-25% ferrite structure, and the percentages are area percentages.
[0008] Furthermore, the steel plate contains dispersed precipitated V(CN), Mo2C, TaC, and Fe3C nanophases with an average size of 12-23nm, the average spacing of these precipitated phases is 1.2-2.5μm, and contains Cu nanophases with an average size of 40-55nm, and the average spacing of the Cu nanophases is 1-3μm.
[0009] Furthermore, the dispersed and precipitated V(CN), Mo2C, TaC, and Fe3C nanophases have a size of 10-30nm, and the Cu nanophase has a size of 30-70nm.
[0010] Furthermore, under room temperature conditions, the yield strength of the steel plate is 510-560 MPa, the yield strength ratio is ≤0.75, and the impact energy at -40°C is not less than 180J.
[0011] Furthermore, the HIC corrosion resistance of the steel plate meets the requirements of CSR≤1%, CLR≤1%, and CTR≤1% after 96 hours of NACEA solution corrosion.
[0012] Furthermore, a cyclic immersion test simulating the seawater splash zone in the southern waters of my country was adopted, and the corrosion resistance was 87-96% relative to the corrosion rate of 3Ni system steel.
[0013] The present invention provides a method for producing lightweight pile steel in a marine environment, including smelting, continuous casting, billet heating, controlled rolling and offline processing, the specific contents of which are as follows:
[0014] Billet heating: The temperature of the cold billet into the furnace is ≤100℃, and multi-stage heating is adopted, wherein the total time of 600-950℃ is controlled within 0.2-0.3min / mm, the total time of 1200-1220℃ is controlled within 0.12min / mm, and the total time of 1170-1200℃ is controlled within 0.2-0.4min / mm;
[0015] Controlled rolling: high temperature direct rolling is adopted, the starting rolling temperature is ≥1050℃, the reduction rate of the first two passes is ≥20%, the average reduction rate of each pass is 12-18%, the final rolling temperature is controlled to be ≥920℃, the cooling rate is controlled to be 3-7℃ / s, and the final cooling temperature is 680-720℃;
[0016] Off-line treatment: After the steel plate is air-cooled off the line, it is stacked or heat-insulated to regulate the second-stage precipitation phase and internal stress, and the insulation regulation temperature is 350-400℃.
[0017] Furthermore, the steel billet is made by converter smelting + continuous casting, and cooling begins when the surface temperature of the steel billet is 820-860°C, and the cooling rate is controlled at 3-10°C / s, followed by low-temperature heating treatment, and the low-temperature heating temperature is controlled at 200-300°C.
[0018] Furthermore, the steel is smelted in a converter, the weight percentage of Ti element in the molten iron is controlled below 0.005%, and Si and Mn are used for deoxidation.
[0019] The lightweight pile steel produced according to the above scheme has the following beneficial effects:
[0020] 1. The corrosion resistance of the steel plate is greatly improved by adding composite trace elements and their synergistic effect. The corrosion resistance is improved by 4-13% compared with the relative corrosion rate (64d) of 3Ni system steel by 87-96% in the simulated seawater splash zone of southern China.
[0021] 2. It has good comprehensive mechanical properties and structural safety, with yield strength of 510-560Mpa, yield strength ratio ≤0.75, and impact energy of not less than 180J at -40℃.
[0022] 3. The anti-HIC corrosion performance meets the requirements of CSR≤1%, CLR≤1%, and CTR≤1% after 96 hours of NACEA solution corrosion.
[0023] 4. There is no crack in the small iron grinding test under 40℃×85%RH environment. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other examples improved or modified by ordinary technicians in this field belong to the scope of protection of the present invention. It should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0025] Aiming at the lightweight requirements faced by large offshore platforms, the present invention develops a steel type that takes into account strength, toughness, weldability, and good resistance to hydrogen-induced cracking through a new component system design and corresponding production process. The corrosion resistance of the steel plate is greatly improved by the addition and synergistic effect of composite trace elements. Under the environmental corrosion conditions in the southern waters of my country, the steel plate that takes into account both the mechanical properties and corrosion properties of steel has a strength of 500MPa and can effectively solve problems such as preventing hydrogen-induced cracking, providing an effective solution for the effective weight reduction of large deep-sea platforms in harsh marine environments such as the southern waters of my country.
[0026] The steel composition of the present invention will be described in detail below. Unless otherwise specified, the content of each element is expressed in % by weight.
[0027] The invention discloses a lightweight pile steel for use in a marine environment. The steel comprises, by weight percentage, C: 0.03-0.06wt%, Si: 0.15-0.3wt%, Mn: 0.7-1wt%, V: 0.04-0.06wt%, N: 0.0012-0.016wt%, Cu: 0.3-0.5wt%, Ni: 0.8-1.2wt%, Mo: 0.2-0.4wt%, Ta: 0.01-0.02wt%, Re: 0.01-0.02wt%, Cr: 1-1.5wt%, REM: 0.03-0.05wt%, Sn: 0.05-0.1wt%, Ti: 0.001-0.005wt%, P: 0.01-0.02wt%, S: ≤0.005wt%, and the balance of Fe and other inevitable impurities.
[0028] C: 0.03-0.06wt%
[0029] The C element is the main phase change controlling element for forming a corrosion-resistant structure with 70-80% bainite + 15-25% ferrite as the matrix, and is also an important element for ensuring the strength of the steel. Appropriate C promotes the formation of important tiny cathode phases V (C, N) and TaC in the present invention. These phases help to improve the corrosion resistance of the steel, especially in a high humidity, high salt environment. More C is not good for the corrosion resistance and weldability of the steel, so the C content is 0.03-0.06wt%.
[0030] Si: 0.15-0.3wt%
[0031] The Si element plays a certain role in strengthening. In addition, it forms surface oxides with Cr, Cu, and Sn, effectively improving corrosion resistance. It is one of the important deoxidizers of the present invention. However, too high Si will reduce the density of the rust layer on the surface of the steel, so the Si content is controlled at 0.15-0.3wt%.
[0032] Mn: 0.7-1wt%
[0033] The Mn element plays a certain role in strengthening and is one of the important deoxidizers of the present invention, so the Mn content is controlled at 0.7-1wt%.
[0034] V: 0.04-0.06wt%
[0035] As an important solid solution and precipitation strengthening element, V element plays an important role in the toughness of steel and is also an important ferrite stabilizing element. The role of V in the present invention is mainly to form V (C, N) with appropriate proportions of C and N. Since the steel material is a multiphase structure formed by multi-element alloying, the control of the cathode ratio in the micro region is very important. The refined, dispersed, uniform and distributed cathode design is very important for controlling the corrosion resistance of the complex structural system of the steel material. Based on this, the present invention adopts a trace amount of 0.04-0.06wt% of V to give full play to its excellent precipitation effect. The electrochemical impedance spectrum shows that after full precipitation, the surface inductive arc of the steel grade is greatly weakened, indicating that the pitting phenomenon is effectively suppressed. It mainly plays the role of controlling the cathode phase. Under the configuration of V, C, N, Cr, Ta and other elements adopted in the present invention, it will promote the generation of 10-30nm dispersed precipitation V (C, N) in the steel matrix, with an average spacing of 1.2-2.5μm, mainly in a spherical shape, which can further prevent the propagation of hydrogen-induced cracks. Based on the above design, the content of V is 0.04-0.06wt%.
[0036] Ta: 0.01-0.02wt%
[0037] On the one hand, Ta element shifts the corrosion potential positively by solid solution, effectively increasing the corrosion potential of the matrix, reducing the corrosion current, and thus improving the corrosion resistance of the steel. On the other hand, it forms 10-30nm TaC, which controls the size and shape of the precipitated phase through precipitation and solid solution, and interacts with V and Cu, thereby improving the steel's resistance to hydrogen-induced cracking.
[0038] N: 0.0012-0.016wt%
[0039] The N element mainly promotes the precipitation of fine particles of V (C, N). In addition, the solid-solution N helps to improve the corrosion resistance of the steel and is beneficial to control the ratio of bainite and ferrite. The N in the present invention is controlled at 0.012-0.016wt%.
[0040] Cu: 0.3-0.5wt%
[0041] Cu is an important corrosion-resistant and toughening element in the present invention. In the early stage of corrosion, when the surface is initially corroded, an enrichment layer and an oxide layer are formed, which improves the non-significant segregation behavior. In addition, a nano phase with an average size of 40-55nm is formed inside the steel plate, and the average spacing between the phases is 1-3μm. After the surface rust layer is destroyed, a large number of fine cathode phases are further formed to form a unique cathode size and distribution control system with V (C, N), TaC, and Fe3C, which controls the corrosion rate and helps to improve and control the weldability. However, too much Cu is not conducive to further exertion of corrosion resistance and increases unnecessary costs. Therefore, the Cu content of the present invention is controlled at 0.3-0.5wt%.
[0042] Ni: 0.8-1.2wt%
[0043] The main function of Ni element is to balance the toughness of weathering steel. In terms of corrosion resistance, it promotes the positive movement of the self-corrosion potential on the steel surface. The present invention adopts a low Mn component design, so that Ni can more effectively promote the formation of Fe3O4 oxides, and Ni in the rust layer 2+ It can more effectively occupy the interstitial position of Fe3O4, forming a stable and dense intermetallic compound of Fe and Ni, preventing Cl - Diffusion into the matrix reduces acidification and increases the pH value of the electrolyte in the rust layer. Since it is used underwater, Ni is controlled at 0.8-1.2wt%.
[0044] Mo: 0.2-0.4wt%
[0045] Mo element can make the rust layer dense, and when combined with Si, Cu, etc., the oxide film formed is effective against initial corrosion. In addition, along with the anodic reaction of steel, MoO4 2- Dissolved, MoO4 on the rust layer 2- distribution, producing ion selection, resisting the corrosion promoting factor Cl - Intrusion. In addition, the addition of Mo helps to improve the low and high temperature stability of the V and Cu dispersed phases, improve their pitting resistance, and the precipitated 10-30nm Mo2C complexes with V (C, N), TaC, and Fe3C, which helps to improve the hydrogen-induced cracking ability of steel. Too high is not good for plasticity. In addition, for high-strength steel, Mo can contribute to the toughness of the steel, so it is controlled at 0.2-0.4wt%.
[0046] Re: 0.01-0.02wt%
[0047] The Re element is evenly distributed in the dendrite trunk and between dendrites during the solidification process. It is an important solid solution strengthening element. Its corrosion potential is about 0.3V, which can shift the corrosion potential positively, effectively increase the corrosion potential of the matrix, reduce the corrosion current of the system, and improve the corrosion resistance of steel. In addition, an appropriate amount of Re combined with Ni and Cu can effectively promote anode passivation and improve cathode efficiency. Since the anode current in the passivation zone is several orders of magnitude smaller than the current of activation and dissolution, it is very effective to use cathodic elements to improve the corrosion resistance of the alloy. The addition of Re helps to improve the low-temperature and high-temperature stability of the dispersed phases of V and Cu. In addition, the compound addition of Re, V, and Ni can effectively control the toughness control problem caused by the addition of elements such as Sn, so it is controlled at 0.01-0.02wt%.
[0048] Cr: 1-1.5wt%
[0049] Cr element plays a role in compacting the rust layer, and on the other hand, it forms a passivating oxide, which, together with other oxides and dense α-FeOOH, resists Cl - Intrusion; In addition, in the composition design of the multi-component system of the present invention, solid solution elements such as Cr are fully dissolved in the matrix, which reduces the solid solubility of V and improves its precipitation behavior, indirectly controlling the thermodynamic and kinetic changes of V (C, N), and after the complex action of Cr, V and other elements forms a stable rust layer, the inductive effect tends to completely disappear, indicating that the material's pitting resistance has reached the best match. According to environmental requirements, the Cr of the present invention is controlled at 1-1.5wt%.
[0050] REM: 0.03-0.05wt%
[0051] On the one hand, REM rare earth elements can change the size of cathode phases such as V (C, N), increase their dispersion, increase their potential, and reduce their cathode effect. Because the content reaches 0.03-0.05wt%, it is fully dissolved in the matrix, which plays a role in increasing the matrix potential and directly produces corrosion resistance. The REM absorbed by grain boundaries, subgrain boundaries, precipitate mismatches and other positions plays a role in balancing the segregation of elements such as Cr and Cu, reducing intergranular and interphase corrosion caused by segregation.
[0052] Ti: 0.001-0.005wt%
[0053] The Ti element helps to control the initial grain size, but too much will consume the N element, affecting the strength and corrosion resistance of the steel. Therefore, the Ti content of the present invention is controlled within 0.001-0.005 wt%.
[0054] Sn: 0.05-0.1wt%
[0055] On the one hand, Sn element reduces the energy level of steel in the form of single substance solid solution and weakens the electrochemical activity of steel. In addition, it helps to form oxides such as SnO and deposit on the corrosion front, promote the formation of α-FeOOH, and compact the oxide layer together with α-FeOOH. When dissolved with Fe, ionic Sn can react with Cl - In combination, the local pH value is increased, the corrosion process is controlled to accelerate, and according to the requirements of the underwater environment, the Sn content of the present invention is controlled at 0.05-0.1wt%.
[0056] P: 0.01-0.02wt%
[0057] The P element is mainly used to reduce the degree of anode polarization, promote the uniform dissolution of steel and accelerate the oxidation rate of iron, promote the formation of non-static protective film, and cooperate with Re, Cu, etc. to resist Cl -However, too much P reduces the weldability of the steel. Taking the converter smelting process as an example, no special control is required. Therefore, the P of the present invention is controlled at 0.01-0.02wt%.
[0058] S: ≤0.005wt%
[0059] Sulfides formed by S element accelerate corrosion and reduce the toughness of steel plate, so it is strictly controlled to ≤0.005wt%.
[0060] In addition to the above-mentioned steel components, the balance of the present invention may be Fe and inevitable impurities. Inevitable impurities are impurities that are not artificially mixed in the general steel manufacturing process. They cannot be completely excluded, and the meaning can be easily understood by those skilled in the art of general steel manufacturing. In addition, the present invention does not completely exclude the addition of other components in addition to the above-mentioned steel components.
[0061] The microstructure of the present invention will be described in further detail below.
[0062] The invention discloses a lightweight pile steel for use in a marine environment. The lightweight pile steel contains a corrosion-resistant structure of 70-80% bainite + 15-25% ferrite, wherein the percentage is the area percentage; the average grain size of a steel plate 1 / 4-1 / 8 in thickness is 20-30 μm, and the average grain size of the steel plate core is 30-50 μm; the steel contains dispersed precipitated V (C, N), Mo2C, TaC, and Fe3C nanophases, wherein the sizes of these precipitated phases are 10-30 nm, the average size is 12-23 nm, and the average spacing is 1.2-2.5 μm; the steel contains dispersed precipitated Cu nanophases, wherein the sizes are 30-70 nm, the average size is 40-55 nm, and the average spacing of the phases is 1-3 μm.
[0063] The production process of the present invention is described in further detail below.
[0064] A method for producing lightweight pile steel in a marine environment, including smelting, continuous casting, billet heating, controlled rolling and offline processing, the specific contents are as follows:
[0065] Smelting: The steel is smelted in a converter; Si and Mn are used for deoxidation, and the use of Al is strictly controlled. The reason is that the addition of Al will consume the N element and have a harmful effect on the surface quality of the steel billet. Similarly, the introduction of the Ti element in the molten iron should also be strictly controlled (controlled to below 0.005%), which affects the precipitation effect of V and Cu and avoids the formation of Ti, Al and other carbonitrides, which is not good for corrosion resistance.
[0066] Continuous casting: The steel billet is made by converter smelting + continuous casting. In order to control the initial surface grain size of the continuous casting billet and the solid distribution of elements such as Re, W, Mo, Cu, Ni, Cr, etc., it plays the role of a dense rust layer. When the billet is discharged, the rapid cooling method is used for pretreatment. The surface temperature of the cold start is controlled at 820-860℃, and the cooling rate is controlled at 3-10℃ / s. After that, it is not suitable for hot loading. Low-temperature heating treatment is required, and the treatment temperature is 200-300℃ to control the surface quality and thermal stress distribution of the steel billet.
[0067] Billet heating: The temperature of the billet cold-charged into the furnace is controlled at ≤100℃, and multi-stage heating is adopted, in which the total time of 600-950℃ is controlled within 0.2-0.3min / mm, the total time of 1200-1220℃ is controlled within 0.12min / mm, and the total time of 1170-1200℃ is controlled within 0.2-0.4min / mm. The purpose is to control the initial distribution of alloy elements and trace elements before hot working. Since the distribution and composition of grains, especially grain boundaries, have a greater impact on corrosion, it is necessary to reasonably control the initial grain size.
[0068] Controlled rolling: The steel plate starts rolling as soon as it leaves the furnace. High-temperature direct rolling is adopted for production. The starting rolling temperature is ≥1050℃, the reduction rate of the first two passes is ≥20%, the average reduction rate of each pass is 12-18%, and the final rolling temperature is controlled to be ≥920℃. The structure and performance are regulated by controlled cooling. The cooling rate is controlled to be 3-7℃ / s. Too fast cooling rate is not conducive to the matching control of toughness and corrosion-resistant structure. The final cooling temperature is 680-720℃. The average grain size of 1 / 4-1 / 8 thickness of the steel plate is controlled to be 20-30μm, and the average grain size of the core of the steel plate is controlled to be 30-50μm to ensure the strength control of the steel. In addition, the importance of this process is to reduce the control deviation of the precipitation phase under the uncontrolled offline thermal history, and to ensure that the components of the main corrosion-resistant elements precipitated in the steel are overcooled to stabilize the precipitation process. In this process, 70-80% bainite + 15-25% ferrite is formed in the steel as the matrix corrosion-resistant structure.
[0069] Off-line processing: After the steel plates are off the line, they are uniformly stacked and heat-insulated to regulate the second-stage precipitation phase and internal stress. Cooling increases the precipitation dynamics of the fine phase, and low-temperature regulation of 350-400°C can be used. On the one hand, the surface hardness can be regulated and the mechanical properties of the steel plate surface can be improved. On the other hand, finer precipitates are formed to improve the overall corrosion resistance of the steel plate.
[0070] After regulation, V (C, N), Mo2C, and TaC with a size of 10-30nm (average size 12-23nm) are dispersed and precipitated in the steel matrix. These are compounded with Fe3C with an average spacing of 1.2-2.5μm. At the same time, there are Cu nanophases with a size of 30-70nm (average size 40-55nm) in the matrix, and the average spacing of the phases is 1-3μm, which plays a role in controlling the comprehensive performance.
[0071] According to the above chemical composition and production process, the actual smelting composition of the present invention is shown in Table 1, the actual process parameters of the present invention are shown in Tables 2-4, and the actual properties are shown in Tables 5-9.
[0072] Table 1 Composition of each example / wt%
[0073]
[0074] Table 2 Pretreatment of blanks
[0075]
[0076] Table 3 Heating process
[0077]
[0078] Table 4 Rolling process
[0079]
[0080]
[0081] Table 5 Steel plate microstructure ratio
[0082]
[0083] Table 6 Mechanical properties of the examples
[0084]
[0085] Table 7 Corrosion resistance of the examples (g / m 2 .h)
[0086]
[0087] Table 8 Anti-HIC performance of the examples
[0088]
[0089]
[0090] The above embodiments were subjected to an inclined Y-groove welding crack test evaluation (Xiaotieyan test) in an environment of 40°C×85%RH. No cracks were found in the dissection results 48 hours after welding.
[0091] Table 9 Experimental results of the small iron grinder in the embodiment
[0092]
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lightweight pile steel for marine environment, characterized in that: The steel composition includes C: 0.03-0.06wt%, Si: 0.15-0.3wt%, Mn: 0.7-1wt%, V: 0.04-0.06wt%, N: 0.0012-0.016wt%, Cu: 0.3-0.5wt%, Ni: 0.8-1.2wt%, Mo: 0.2-0.4wt%, Ta: 0.01-0.02wt%, Re: 0.01-0.02wt%, Cr: 1-1.5wt%, REM: 0.03-0.05wt%, Sn: 0.05-0.1wt%, Ti: 0.001-0.005wt%, P: 0.01-0.02wt%, S: ≤0.005wt%, and the balance is Fe and other inevitable impurities; The average grain size of 1 / 4-1 / 8 thickness of the steel plate is 20-30μm, the average grain size of the core of the steel plate is 30-50μm, the steel plate contains 70-80% bainite + 15-25% ferrite structure, and the percentage is area percentage; the steel plate contains V (C, N), Mo2C, TaC, Fe3C nanophases with an average size of 12-23nm dispersed and precipitated, the average spacing of these precipitated phases is 1.2-2.5μm, and contains Cu nanophases with an average size of 40-55nm, and the average spacing of the Cu nanophases is 1-3μm; the size of the dispersed precipitated V (C, N), Mo2C, TaC, Fe3C nanophases is 10-30nm, and the size of the Cu nanophase is 30-70nm.
2. The lightweight pile steel for marine environment according to claim 1, characterized in that: Under room temperature conditions, the yield strength of the steel plate is 510-560MPa, the yield strength ratio is ≤0.75, and the impact energy at -40℃ is not less than 180J.
3. The lightweight pile steel for marine environment according to claim 1, characterized in that: The steel plate's HIC corrosion resistance meets the requirements of CSR≤1%, CLR≤1%, and CTR≤1% after 96 hours of NACEA solution corrosion.
4. The lightweight pile steel for marine environment according to claim 1, characterized in that: A cyclic immersion test simulating the seawater splash zone in the southern waters of my country was adopted, and the corrosion resistance was 87-96% relative to the 3Ni system steel.
5. A method for producing lightweight pile steel in marine environment according to any one of claims 1 to 4, characterized in that: It includes smelting, continuous casting, billet heating, controlled rolling and offline processing. The specific contents are as follows: Billet heating: The billet is cold loaded into the furnace at a temperature of ≤100°C, and multi-stage heating is adopted, wherein the total time at 600-950°C is controlled within 0.2-0.3min / mm, the total time at 1200-1220°C is controlled within 0.12min / mm, and the total time at 1170-1200°C is controlled within 0.2-0.4min / mm; Controlled rolling: high temperature direct rolling is adopted, the starting rolling temperature is ≥1050℃, the reduction rate of the first two passes is ≥20%, the average reduction rate of each pass is 12-18%, the final rolling temperature is controlled to be ≥920℃, the cooling rate is controlled to be 3-7℃ / s, and the final cooling temperature is 680-720℃; Off-line treatment: After the steel plate is air-cooled off the line, it is stacked or heat-insulated to regulate the second-stage precipitation phase and internal stress, and the insulation regulation temperature is 350-400℃.
6. The method for producing lightweight pile steel in marine environment according to claim 5, characterized in that: The steel billet is made by converter smelting + continuous casting. The steel billet starts to cool when the surface temperature is 820-860°C, and the cooling rate is controlled at 3-10°C / s. It is then subjected to low-temperature heating treatment, and the low-temperature heating temperature is controlled at 200-300°C.
7. The method for producing lightweight pile steel in marine environment according to claim 5, characterized in that: The steel is smelted in a converter, the weight percentage of Ti element in molten iron is controlled below 0.005%, and Si and Mn are used for deoxidation.
Citation Information
Patent Citations
High-strength high dampness and heat sea atmospheric environment resistant weathering resistant steel and preparing method
CN106756476A
High-damp-heat-resistant marine atmosphere high-strength weathering resistant steel
CN106756602A
High-anticorrosion low alloy steel suitable for high-temperature littoral environment
CN106929751A
Steels with excellent resistance to hydrogen-induced cracking and their manufacturing methods
CN111527227B
580 MPa grade marine engineering steel with low stress corrosion sensitivity and production method thereof
CN110629102A